Global Research Trends on Environmental, Social and Governance: A Bibliometric Analysis - Inayati, Nur Isna; Isthika, Wikan; Sulistiyanti, Umi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
Companies engage in ESG activities to achieve higher financial returns and to signal compliance in the market. The link between ESG and corporate financial performance is still not well established because much of the literature contains conflicting results and paradoxes. Through bibliometric analysis and meta-analysis, this research seeks to synthesize the literature on ESG performance and its impact on performance. Bibliometric analysis highlights leading scholars in the field, leading journals, institutions, countries, and an overview of highly cited articles in the field of sustainable finance. This study presents research trends and a future research framework is proposed based on the research gaps identified in this review.